2010
DOI: 10.1074/jbc.m109.081380
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Framework of Selenocysteyl-tRNASec Recognition by Elongation Factor SelB

Abstract: Sec selection and rapid release of Sec-tRNA Sec from SelB after GTP cleavage on the ribosome. SelB provides an example for the evolution of a highly specialized protein-RNA complex toward recognition of unique set of identity elements. The mode of tRNA recognition by SelB is reminiscent of another specialized factor, eIF2, rather than of EF-Tu, the common delivery factor for all other aminoacyl-tRNAs, in line with a common evolutionary ancestry of SelB and eIF2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
62
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 38 publications
0
62
1
4
Order By: Relevance
“…(IF1, IF2, IF3), and fMet-tRNA fMet were prepared as described [47][48][49] . E. coli SelA and SelD (gift from M. Wahl, Free University of Berlin) and SelB 50 containing a hexahistidine tag (gift from A. Böck, LMU Munich) were expressed in BL21(DE3) cells and purified according to published protocols 4,51 . Biochemical analysis showed that SelB carrying the His-tag is fully functional in the interactions with guanine nucleotides, SECIS elements, and Sec-tRNA Sec and in mediating UGA recoding in vivo 4,50 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(IF1, IF2, IF3), and fMet-tRNA fMet were prepared as described [47][48][49] . E. coli SelA and SelD (gift from M. Wahl, Free University of Berlin) and SelB 50 containing a hexahistidine tag (gift from A. Böck, LMU Munich) were expressed in BL21(DE3) cells and purified according to published protocols 4,51 . Biochemical analysis showed that SelB carrying the His-tag is fully functional in the interactions with guanine nucleotides, SECIS elements, and Sec-tRNA Sec and in mediating UGA recoding in vivo 4,50 .…”
Section: Discussionmentioning
confidence: 99%
“…E. coli SelA and SelD (gift from M. Wahl, Free University of Berlin) and SelB 50 containing a hexahistidine tag (gift from A. Böck, LMU Munich) were expressed in BL21(DE3) cells and purified according to published protocols 4,51 . Biochemical analysis showed that SelB carrying the His-tag is fully functional in the interactions with guanine nucleotides, SECIS elements, and Sec-tRNA Sec and in mediating UGA recoding in vivo 4,50 . tRNA Sec was overexpressed in E. coli BL21 transformed with the plasmid pCB2013 (gift from A. Böck, LMU Munich) 52 and purified and aminoacylated as described 4,53,54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations